Chiral Unsymmetrically Substituted Bipyridine N, N′‐Dioxides as Catalysts for the Allylation of Aldehydes. Issue 37 (17th July 2018) - Ulč, Jan; Nečas, David; Koukal, Petr; Havlíček, Vojtěch; Tošner, Zdeněk; Hybelbauerová, Simona; Kotora, Martin
Abstract : A series of unsymmetrically substituted diastereoisomeric ( Ra, R ) and ( Sa, R ) bipyridine N, N′ ‐dioxides was synthesized by using oxidative coupling of the corresponding metallated tetrahydroisoquinoline N ‐oxides in the presence of iodine. The N, N′ ‐dioxides contained substituted aryl groups with electron‐donating or electron‐accepting groups in the near vicinity of the N, N′ ‐dioxide moiety. Their catalytic activity was tested in a series of reactions of allyltrichlorosilane with various substituted benzaldehydes, thiophenecarbaldehyde, and cinnamaldehyde. The reactions proceeded with high enantioselectivities (up to 98 % ee ) with catalyst loadings as low as 0.5 mol‐%. Furthermore, allylation reactions of ( E )‐3‐iodomethacrylaldehyde were also carried out to give chiral ( E )‐1‐iodo‐2‐methylpenta‐1, 4‐dien‐3‐ol, a convenient building block for the synthesis of natural products. The allylations proceeded with high enantioselectivities (up to ca. 99 % ee ) with a catalyst loading of 2.5 mol‐%. Abstract : A series of unsymmetrically substituted diastereoisomeric ( Ra, R ) and ( Sa, R ) bipyridine N, N′ ‐dioxides were tested as catalysts for the enantioselective allylation of various aldehydes. Homoallylic alcohols were obtained with enantiopurities of up to 99 % ee .